The National Research Clearance Process - The Uganda National Council for Science and Technology (UNCST, 2021)
Oversight of research is done first at the institutional level by Research Ethics Committees (RECs), Institutional Animal Care and Use Committees (IACUCs), Uganda Wildlife Authority (UWA), National Forest Authority (NFA) and any other authorized lead agencies then second at the national level by the Uganda National Council for Science and Technology (UNCST) in collaboration with Uganda National Health Research Organization (UNHRO). UNCST liaises with the research secretariat, Office of the President to obtain security verification and clearance for the researcher. An additional requirement with regard to clinical trials is for the researcher to obtain a certificate from the National Drug Authority (NDA) in respect of a trial drug.
Keywords: Research Clearance Process